Countering hybrid threats : lessons learned from Ukraine. - Iancu, Niculae; Fortuna, Andrei; Barna, Cristian; Teodor, Mihaela (NATO science for peace and security series. Human and societal dynamics, 2016)
"This book contains 28 articles on the topic of hybrid warfare and related threats, delivered at the NATO Advanced Research Workshop (ARW) 'Countering Hybrid Threats: Lessons Learned from Ukraine', held in Bucharest, Romania, in September 2015. This event brought together 50 experts from different fields and perspectives, including policymakers, security and intelligence practitioners, and academics. The presentations explored the nature of the Ukrainian conflict and the dynamic evolution of current security threats in Central and Eastern Europe and the Black Sea region with the aim of identifying the key drivers of the conflict and exploring the most efficient instruments and methods for conflict resolution"--Page 4 of cover.